MAPping tubulin mutations - Cushion, Thomas D.; Leca, Ines; Keays, David A. (Frontiers in Cell and Developmental Biology, 2023)
Microtubules are filamentous structures that play a critical role in a diverse array of cellular functions including, mitosis, nuclear translocation, trafficking of organelles and cell shape. They are composed of /-tubulin heterodimers which are encoded by a large multigene family that has been implicated in an umbrella of disease states collectively known as the tubulinopathies. De novo mutations in different tubulin genes are known to cause lissencephaly, microcephaly, polymicrogyria, motor neuron disease, and female infertility. The diverse clinical features associated with these maladies have been attributed to the expression pattern of individual tubulin genes, as well as their distinct function repertoire. Recent studies, however, have highlighted the impact of tubulin mutations on microtubule associated proteins (MAPs). MAPs can be classified according to their effect on microtubules and include polymer stabilizers (e.g., Tau, MAP2, DCX), destabilizers (e.g., spastin, katanin), plus-end binding proteins (e.g., EB1-3, XMAP215, CLASPs) and motor proteins (e.g., dyneins, kinesins). In this review we analyse mutation-specific disease mechanisms that influence MAP binding and their phenotypic consequences, and discuss methods by which we can exploit genetic variation to identify novel MAPs.